Analisis Faktor Pengaruh Contribution Margin Terhadap Perencanaan Penjualan “Franchise Mixue Karangjati, Kabupaten Semarang” - Fiktor Ardin Halawa; Dyah Palupiningtyas (Universitas Sains dan Teknologi Komputer, 2024)
This study aims to analyze the best-selling ice cream sales data in 2022 from the Mixue Karangjati franchise in Semarang Regency, as well as calculate the contribution margin ratio (RCM) and break-even point (BEP) in units and monetary value for each item. Sales data and related costs are processed to gain insights into the company's financial performance. The analysis results indicate that the RCM for the year 2022 is 7.4%, while the BEP in units and monetary value has been calculated for each item. Additionally, planning recommendations for the future are provided, including product diversification, cost monitoring, technology utilization, and service quality improvement. This study provides crucial insights for management in financial planning and strategic decision-making to achieve the company's business goals.